2014
DOI: 10.15306/mvpjms/2014/v1i2/52031
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Evaluation by Histopathology in Abnormal Uterine Bleeding in Perimenopausal and Postmenopausal Patients

Abstract: Introduction: Abnormal Uterine Bleeding (AUB) is an important symptom of both benign and serious gynaecological diseases. Abnormal perimenopausal or postmenopausal bleeding is associated with endometrial carcinoma in approximately 10% of cases. The present study is designed to study the histopathological results of the endometrial biopsy in women with abnormal perimenopausal and postmenopausal uterine bleeding. Aims and Objectives: To study, the various histopathological patterns of endometrium, in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As the risk of endometrial carcinoma increases with age, the American College of Obstetricians and Gynecologists recommends endometrial evaluation in women aged 35 years and older who have abnormal uterine bleeding [2,6]. Endometrial carcinoma thus is commonly seen in the peri-and post menopausal age group [13,14] and post menopausal bleeding in women receiving hormone therapy for more than 12 months definitely needs endometrial study to rule out carcinoma. The incidence of carcinoma is low in our study like Doraiswamy et al and Rupal Shah et al probably because of early detection, but higher in other studies -Divya and Sajita et al…”
Section: Discussionmentioning
confidence: 99%
“…As the risk of endometrial carcinoma increases with age, the American College of Obstetricians and Gynecologists recommends endometrial evaluation in women aged 35 years and older who have abnormal uterine bleeding [2,6]. Endometrial carcinoma thus is commonly seen in the peri-and post menopausal age group [13,14] and post menopausal bleeding in women receiving hormone therapy for more than 12 months definitely needs endometrial study to rule out carcinoma. The incidence of carcinoma is low in our study like Doraiswamy et al and Rupal Shah et al probably because of early detection, but higher in other studies -Divya and Sajita et al…”
Section: Discussionmentioning
confidence: 99%
“…Perimenopause is the phase, preceding the onset of menopause, generally occurring around 40 years of age during which the regular menstrual cycle of a woman changes from normal cycles to a pattern of irregular cycles. [1] Menopausal transition includes a period of about 4-5 years before menopause, sometimes even several months, characterized by varying degrees of somatic and psychological changes that reflect the changes in the ovarian cycle. [1] In some women, the most significant symptom is an irregular menstrual period, which must be carefully evaluated to determine whether it is the consequence of low oestrogen levels or an associated pathology.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Menopausal transition includes a period of about 4-5 years before menopause, sometimes even several months, characterized by varying degrees of somatic and psychological changes that reflect the changes in the ovarian cycle. [1] In some women, the most significant symptom is an irregular menstrual period, which must be carefully evaluated to determine whether it is the consequence of low oestrogen levels or an associated pathology. [1] Abnormal uterine bleeding (AUB) is one of the most common and challenging problems presenting to the gynaecologist.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In our study, endometrial carcinoma was found in a 63-year-old lady who presented with postmenopausal bleeding. It has been reported in 2.48% of all patients with AUB by Vaidya et al and 2.0% by Desai et al [15,1] Endometrial carcinoma mostly occurs in elderly women (Sixth and seventh decade) with 90% of patients presenting with vaginal bleeding or discharge as a presenting complaint. [1] CONCLUSION Endometrial histopathology in abnormal uterine bleeding is an important tool to diagnose various endometrial patterns ranging from proliferative, secretory, simple and complex hyperplasia with/without atypia, disordered proliferation and atrophic endometrium, including pathologic conditions of uterus including hyperplasia and carcinoma of endometrium, especially in perimenopausal and postmenopausal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[1] AUB in reproductive age women is defined as bleeding at abnormal or unexpected times or by excessive flow at the time of an expected menses. The aetiology of abnormal genital bleeding encompasses a wide range of disorders that can be secondary to anatomic changes of female genital tract, infection, endocrinologic disorders, malignancies, systemic illness.…”
Section: Introductionmentioning
confidence: 99%